Kedudukan Surat Edaran Gubernur Aceh Nomor 450/21770 Tentang Larangan Mengadakan Pengajian Selain Dari I’tiqad Ahlussunnah Waljamaah Yang Bersumber Dari Mazhab Syafi’iyah Terhadap Qanun Nomor 8 Tahun 2014 Tentang Pokok-Pokok Syariat Islam - Muhammad Nur Miswari; Faisal Akbar Nasution; Mirza Nasution; Chairul Bariah (Iuris Studia: Jurnal Kajian Hukum, 2021)
The provisions of Permendagri Number 55 of 2010 concerning Administration of Service Scripts within the Ministry of Home Affairs Article 1 43 states that Circular Letters are official texts containing notifications, explanations, and/or instructions based on how to carry out certain things that are considered important and urgent. Then in the Regulation of the Head of the National Archives of the Republic of Indonesia Number 2 of 2014 concerning Guidelines for Official Manuscripts, circulars are classified as products of official manuscripts. So ideally the Circular Letter is only a communication tool in the form of notification to internal circles. The issuance of the Circular Letter of the Governor of Aceh Number 450/21770 concerning the Prohibition of Holding Recitations Other than I'tiqad Ahlussunnah Waljamaah which is sourced from the Syafi'iyah School of Law by the Acting Governor of Aceh has created a new problem, namely the forcible dissolution of the recitation by a group calling itself a warrior. ASWAJA, as well as the Aceh Governor's Circular has reduced the rights of citizens protected by the constitution, the Head of the Aceh Ombudsman gave the opinion that the SE was revoked by the issuance of the SE it would lead to intolerance between religious communities and enter the realm of maladministration. The approach method in this research is using a sociological juridical method using a statute approach, a historical approach, and a case approach. The results of research from the Aceh government in making policies were formed by the Aceh People's Representative Council (DPRA) and the Aceh Governor on the advice and input of the MPU, but in terms of the formation of the SE issued by the Aceh Governor this is a regulation that comes from freies ermessen or discretion it is only an official document. Thus, the SE needs to be supervised by the Ombudsman, DPRA, and also the State Administrative Court as an institution in the public service.